Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

IF CosX+SinX=?2.CosX P.T CosX-SinX=?2.SinX

Asked by chethan U 22nd July 2012, 5:33 PM
Answered by Expert
Answer:
Answer : Given : cosA+ sinA = (underroot2 )*cosA 
To prove : cosA - sinA = (underroot2 )*sinA
 
we have ,
=> (cosA+sinA)2 + (cosA -sinA) = 2
=> ( (underroot 2 ) *(cosA) ) + (cosA-sinA)= 2  { using given equation}
=> 2cos2A + (cosA-sinA)2 = 2  
=> (cosA-sinA)= 2 - 2cos2A
=> (cosA - sinA)2 = 2 ( sin2A )    { using 1 - cos2A = sin2A }
 
taking the square root both the sides we get ,
 
=>  cosA- sinA = (underroot2 )*sinA
            Hence Proved 
Answered by Expert 22nd July 2012, 7:41 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!